0129 Gauging The Gap In Key Patient Safety Skills And Behaviours Amongst Undergraduate Medical Students. (1st November 2014) - Kirton, Ella-Grace; Woodier, Nicholas; Poynton-Smith, Emma; Ferguson, Eamonn; Baxendale, Bryn
Abstract : Background: Newly qualified medical staff should be able to contribute to patient safety and quality improvement although this potential is often not optimised. Knowledge and attitudes to patient safety amongst junior doctors has been scrutinised but analysis of weaknesses in safety skills and behaviours is less evident. This project aimed to explore this area in final year medical students at the University of Nottingham. Methodology: A long-list of skills and behaviours was compiled from published patient safety curricula. An expert group of local educators and clinicians experienced in patient safety reviewed these using a modified nominal group Delphi method and prioritised those deemed most important or difficult to attain in medical undergraduates before qualification. A cohort of final year undergraduate medical students were asked to self-rate (five point Likert scale) their ability to demonstrate these skills and behaviours if required when commencing as an FY1 doctor. Students were also asked to consider how they expected these attributes to have altered by the end of their FY1 year. Results: The expert group identified 20 prioritised safety skills and behaviours. Survey responses from 41 undergraduates indicated students felt more capable of communication related skills in terms of informing patients about harm events, although less able to challenge or raise concerns about colleagues' performance. Students felt less able to report or engage in analysis of patient safety incidents. Use of quality improvement techniques was an area of unfamiliarity. Students expected to be able to perform all skills and behaviours better by the end of the FY1 year. Conclusions and recommendations: This project highlighted safety skills and behaviours for prioritisation in future educational interventions, which could use simulation-based approaches for development and assessment of attaining suitable standards of performance. This could also expose areas of unconscious incompetence in undergraduates as they prepare for practice. References: Durani P, Dias J, Singh HP, Taub N. 'Junior doctors and patient safety: evaluating knowledge, attitudes and perception of safety climate.' BMJ Qual Saf 2013; 22(1):65–71 General Medical Council, Tomorrow's Doctors 2009 Vohra PD, Johnson JK, Daugherty CK, Wen M, Barach P. 'Housestaff and medical student attitudes toward medical errors and adverse events' Jt Comm J Qual Patient Saf . 2007 33(8):493–501